The winter guest - Jenoff, Pam (Mira Books, 2014)
When Helena discovers an American paratrooper stranded outside their small mountain village, wounded, but alive, she risks the safety of herself and her family, to hide Sam--a Jew. Soon her concern for the American grows into something much deeper--an attraction that will culminate in a singular act of betrayal that endangers them all--and sets in motion a chain of events that will reverberate across continents and decades.